PELAKSANAAN PROGRAM VAKSINASI KEPADA MASYARAKAT TERKAIT EFEKTIVITAS PENANGANAN COVID-19 DI PADEMANGAN JAKARTA UTARA - Iqbal Aidar Idrus; Rachmat Widiharto Haryadi Widiharto (Department of Public Administration, Faculty of Social and Political Science, Universitas, 2023)
The lack of public trust in the Pademangan District of North Jakarta in the Covid-19 Vaccination is one of the obstacles in providing public services to break the chain of the Covid-19 pandemic. Likewise, the level of public awareness of Pademangan District in terms of Health is very low, and there is still a lack of education and socialization about vaccination from related agencies. The public does not even know the benefits of the Covid19 vaccination. This is what motivated the author to provide knowledge about Covid-19 vaccination with the Miles and Huberman method (1984). This study aims to determine how effective the implementation of the Covid-19 vaccination at the Pademangan District Health Center is to the community. The method used is a descriptive qualitative approach. This research uses a case study approach that focuses on one particular unit of various phenomena. The choice of research with a case study approach is because it can examine deep and factual problems. The instrument used in this research is in the form of data collection methods such as interviews, documentation, and observations. Objective: The purpose of this study was to determine the effectiveness of the implementation of the Covid19 vaccination at the Pademangan District Health Center, North Jakarta. The results of this research show that according to the analytical tools of the indicators of the effectiveness of the Covid-19 vaccination program, namely: Productivity of health workers and related agencies, Quality of Covid-19 vaccination, Efficiency in providing services, Flexibility in change, Community satisfaction in services. Vaccination, Excellence in serving the community, Development of the Pademangan District Health Center, North Jakarta. The implementation of the Covid-19 Vaccination program has been achieved quite well based on the measurement of program indicators so that the implementation of government programs in the Health sector at the Pademangan District Health Center in providing services to the community of prospective Covid-19 Vaccination participants is quite effective. In its implementation, it is still found inhibiting factors originating from the community and must be overcome in order to break the Covid-19 chain, so that services can run well and cooperation is formed between service providers and service users.